Relationship between Changes in Physicochemical Properties with Antioxidant and Antitumor Activity Changes in Vitro of Different Purified Fractions of Pu-erh Tea Polysaccharides - Yilong WU; Zaikun SHUI; Yan WANG; Zhenhao LIU; Xuanjun WANG; Chengting ZI (Shipin gongye ke-ji)
To investigate the effects of changes in physicochemical properties on the in vitro antioxidant and antitumor activities of different purified fractions of Pu-erh tea polysaccharides (PTPS), PTPS were isolated and purified using Pu-erh raw tea as the raw material, the patterns of changes in the physicochemical properties of different fractions of PTPS were analyzed, the in vitro antioxidant and antitumor activities of the fractions were studied, and the correlation between changes in the physicochemical properties and changes in the antioxidant and antitumor activities of different purified fractions was investigated through correlation analysis. Results showed that the physicochemical properties of the five fractions (PTPS 1~5) obtained after purification varied significantly. The mean degree and total sugar content of PTPS 1~5 were observed to increase and then decrease as the concentration of NaCl in the eluent was increased, whereas the particle size and polydispersity index were found to exhibit the opposite pattern, manifesting as a decrease followed by an increase. The protein content, uronic acid content, and esterification degree were shown to have an overall increasing trend, while the average molecular weight and Zeta potential were not found to display obvious regularity. Differences in the physicochemical properties of PTPS were found to lead to differences in antioxidant and antitumor activities in vitro. The results of Pearson correlation analysis showed that the indicators of the physicochemical properties of the different purified fractions were closely correlated with the average degree, the average molecular weight, the total sugar content, the uronic acid content, the esterification degree, and polydispersity index value, while the antitumor activities were mainly correlated with the total sugar content, the uronic acid content, and the esterification degree. The results of this study may provide theoretical support for the application of PTPS in the field of bioactive polysaccharides and functional foods.